2017
DOI: 10.1136/jim-2016-000404
|View full text |Cite
|
Sign up to set email alerts
|

A Dab2Ip Genotype: Sex Interaction is Associated with Abdominal Aortic Aneurysm Expansion

Abstract: A faster expansion rate of abdominal aortic aneurysm (AAA) increases the risk of rupture. Women are at higher risk of rupture than men, but the mechanisms underlying this increased risk are unknown. We investigated whether genetic variants that influence susceptibility for AAA (, ,, and) are associated with AAA expansion and whether these associations differ by sex in 650 patients with AAA (mean age 70±8 years, 17% women) enrolled in the Mayo Clinic Vascular Disease Biorepository. Women had a mean aneurysm exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…The present study was able to confirm that the T allele also had an association with mortality, but only in one of the two genders. Ye et al (28) in a study of abdominal aneurysms, demonstrated significant sex differences, where a faster expansion of the aneurysms could be seen in the female group and therefore the present study intended to evaluate any sex differences in CV mortality in the different genotypes of rs1466535.…”
Section: Discussionmentioning
confidence: 98%
“…The present study was able to confirm that the T allele also had an association with mortality, but only in one of the two genders. Ye et al (28) in a study of abdominal aneurysms, demonstrated significant sex differences, where a faster expansion of the aneurysms could be seen in the female group and therefore the present study intended to evaluate any sex differences in CV mortality in the different genotypes of rs1466535.…”
Section: Discussionmentioning
confidence: 98%
“…In particular the authors hypothesised that oscillatory shear stress is a specific signal to the endothelium, which initiates the events leading to AAA formation, and that sex-dependent differences in oscillatory shear stress in the infrarenal aorta may explain the gender-related differences. Ye et al 39 investigated the potential influence of genetic variants on susceptibility to AAAs (CDKN2A-2B, SORT1, DAB2IP, LRP1 and LDLR), and their association (particularly gender-related) with AAA expansion. In a population of 650 patients affected by AAA, the authors demonstrated that women had a mean greater aneurysm expansion than men after adjustment for baseline AAA diameter.…”
Section: New Hypotheses On Gender Differencesmentioning
confidence: 99%
“…Ye et al. 39 investigated the potential influence of genetic variants on susceptibility to AAAs (CDKN2A-2B, SORT1, DAB2IP, LRP1 and LDLR), and their association (particularly gender-related) with AAA expansion. In a population of 650 patients affected by AAA, the authors demonstrated that women had a mean greater aneurysm expansion than men after adjustment for baseline AAA diameter.…”
Section: Abdominal Aortic Aneurysmsmentioning
confidence: 99%
“…It mainly occurs in the last decades of life and predominantly affects the male gender [2]. A ruptured AAA leads to a high mortality rate of up to 80% [3,4]. The risk of developing AAA increases with hypertension, dyslipidemia, and a history of smoking [5,6].…”
Section: Introductionmentioning
confidence: 99%